THE PHENOMENON OF HEALTH JUDICIALIZATION FROM THE PERSPECTIVE OF PUBLIC DEFENDERS: A CASE STUDY ON THE ARID AND REMOTE INTERIOR OF PERNAMBUCO - Freire, Phablo; de Andrade Acioli, Yago (LINKSCIENCEPLACE, 2026)
The present work aims to provide a discussion about the conceptual issues surrounding the phenomenon of health judicialization, being chosen as a resource for both the analysis of the experience of a Public Defender in personal contact with this problem, from his narrative, so that It is possible to delimit a concept that is at once theoretical and pragmatic about the phenomenon of health judicialization. About the method, the research is located in the legal-sociological theoretical, legal-descriptive type of qualitative character. Data were collected through a semi-structured interview, and the discourse analysis technique was adopted for the examination. It was concluded that the judicialization can be understood as a juridical phenomenon based on the constitutional dictates, which are configured as advanced norms in the scenario of recognition of social rights, which results in the perspective of legitimacy of the action that is aimed at realizing such rights, result Of a poor public management, which is its cause and affects the majority of the population, perceived both in contexts of underdevelopment, and because of the perversity of the conduct of public policies.